“MOTIVATION” AND “GOD-IMAGE” OF INDONESIAN MIGRANT WORKERS IN HONG KONG - Kristiyanto, Nikolas; Warsono, Agustinus Tri Edy; Subali, Yohanes; Manggala, Jakobus Aditya Christie; Haryadi, Dominikus Setio (Journal of Asian Orientation in Theology, 2024)
This paper explores the motivations and perceptions of God among Indonesian migrant workers in Hong Kong, focusing on their unique experiences and faith struggles. The study, guided by Interpretative Phenomenological Analysis (IPA), is based on the narratives of five female migrant workers with 6-12 years of experience in Hong Kong. From our study, compassion is identified as a fundamental motivator for Indonesian migrant workers. The study finds that all respondents maintain a positive God-Image, perceiving God as their Helper, Caregiver, and source of strength. Their faith is identified as a core motivation for survival. The Good Samaritan (Luke 10:25-37) is employed to illustrate this approach. Finally, this paper tries to contribute to offering a unique perspective on the lives of Indonesian migrant workers in Hong Kong, emphasizing the critical roles of compassion, faith, and a positive God-image in their experiences, and promoting a fresh approach to addressing their struggles.